2001
DOI: 10.1162/105864001316907964
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of Overconfidence and Entrepreneurs

Abstract: This paper explains why seemingly irrational overcon dent behavior can persist. Information aggregation is poor in groups in which most individuals herd. By ignoring the herd, the actions of overcon dent individuals ("entrepreneurs") convey their private information. However, entrepreneurs make mistakes and thus die more frequently. The socially optimal proportion of entrepreneurs trades off the positive information externality against high attrition rates of entrepreneurs, and depends on the size of the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(209 citation statements)
references
References 12 publications
8
198
1
2
Order By: Relevance
“…For an entry to some of the topics that we have not discussed, see Bernardo & Welch (2001) and Robson (2002Robson ( , 2003 …”
Section: Discussionmentioning
confidence: 99%
“…For an entry to some of the topics that we have not discussed, see Bernardo & Welch (2001) and Robson (2002Robson ( , 2003 …”
Section: Discussionmentioning
confidence: 99%
“…It is this optimism that tends to be greater when individuals have emotional commitment to the results of their work. Bernardo & Welch (2001) found that by providing positive information externally to their social group, over-confident entrepreneurs are more preferred by their environment. If these externalities are significant enough, then social welfare will be increased through having some over-confident people in the population, even though such people are not behaving in an optimal way as regards their own welfare.…”
Section: Decision Making: Heuristics and Errorsmentioning
confidence: 96%
“…Consider how over-confident entrepreneurs contribute positively to the evaluations of Π e ijt and to social welfare. Over-confident entrants, even if after some periods they exit the market, representing in this way a waste of resources from a social point of view, are a benefit to the society as a whole (Bernardo & Welch, 2001;Dosi & Lovallo, 1997). Exploring new ways of doing something reduces the probability of having phenomena of lock-in and possible local path-dependency to sub-optimal equilibria.…”
Section: Profits Psychological Effects and Informationmentioning
confidence: 99%
“…Superior innovations might diffuse if there were overoptimistic entrepreneurs who pay the price of the initial exploration: Their failure opens the way to the takeoff of the industry (Dosi & Lovallo, 1997). If we consider a model of herd behaviour (or informational cascade), in which two types of individuals, normal ones and entrepreneurs (over-confident individuals that are more likely to follow their signal, disregarding other people's public choices), are asked to undertake an action or not on the basis of their signals, it emerges that in the absence of entrepreneurs the phenomenon of herd behaviour soon emerges in the decision process and individuals typically end up following the same action regardless of their private signal, thus revealing no new information to the public (Bernardo & Welch, 2001). On the contrary, in the presence of over-confident individuals, it is more likely that the chain of herd behaviour will be broken, in this way avoiding the pitfall that the whole society could converge on the incorrect (or inferior) choice (wrong informational cascade).…”
Section: Profits Psychological Effects and Informationmentioning
confidence: 99%